การวิเคราะห์การคงอยู่ของกรมธรรม์ประกันชีวิตประเภทสามัญ - วรัญญา เกียรติวิทู (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
The objectives of this study were to estimate the survival functions, an average, a median of the terminated ordinary life insurance policy years; to compare the survival function within each factors affecting the life insurance policy life time; and to determine the impact of factors affecting the life insurance policy life time. The data for this study were collected from one of the life insurance companies in Thailand. This data set was based on all of the individual life insurance policies terminated in the year 2001. Estimation of the survival functions, an average, a median of the terminated ordinary life insurance policy years by using Product-Lim it Method, showed that most of life insurance policies terminated between 1-1.13 year. In addition, the average life time of terminated life insurance policies was 1.20 year and the median life time was only 1.08 year. The results of comparing the survival function within each factor w h ich had the influence on the life time of insurance policies by using survival curves, Gehan’s Gereralized Wilcozon Test, and Log Rank Test, found that the attained age of whom insured, sex, plan of insurance, mode of payment, sum insured, period insured, period of payment, classify of risk, rid er and distribution of life insurance company had the difference survival life time at statistical significant 0.05. The data analyzed by using multivariate parametric model at statistical significant of 0.05, found that the survival life time for policies issued to female were higher than those of policies issued to male. Whole -life policies had survival life time which was not different with term policies, but having higher than endowment policies and annuity policies. The survival life time for the small sum insured was low e r than that of the large sum insured. Regarding the survival life time of the period insured, there was not any difference between period insured 0-20 years and 36-55 years, but it was low er than 21-35 years and over 55 years. Period of payment in 20 years and below had the survival life time better than that of above 20 years. Besides, standard risk of insured had have the survival life time better than substandard risk which is the same as non-rider policies that had this life time better than the policies with riders. Finally, policies issued by branches of life insurance company located in Bangkok area had the survival life time better than those issued by the branches w h ich located in the Northen area, the Central area (excluding Bangkok), the Northeasten and especially the Southen regions.